2023
DOI: 10.3390/cells12131799
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Kinase Inhibition Attenuates Neuroinflammation and Cytotoxicity in Animal Models of Alzheimer’s and Parkinson’s Disease-Related Neuroinflammation

Abstract: Chronic neuroinflammation plays a crucial role in the progression of several neurodegenerative diseases (NDDs), including Parkinson’s disease (PD) and Alzheimer’s disease (AD). Intriguingly, in the last decade, leucine-rich repeat kinase-2 (LRRK2), a gene mutated in familial and sporadic PD, was revealed as a key mediator of neuroinflammation. Therefore, the anti-inflammatory properties of LRRK2 inhibitors have started to be considered as a disease-modifying treatment for PD; however, to date, there is little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This inhibition effectively alleviates neuroinflammationinduced dopaminergic neuronal loss in various experimental models, including mouse glioma cells, primary rat microglia, and human microglia cell lines [42]. Furthermore, studies have demonstrated that LRRK2 kinase inhibition attenuates neuroinflammation, gliosis, and cytotoxicity in murine models receiving intracerebral injections of α-syn preformed fibrils, thereby reinforcing the anti-inflammatory potential of LRRK2 kinase inhibition in preclinical settings [43]. Recent investigations employing a chimeric mouse model revealed that replacing mutant LRRK2 with the wild-type variant of the protein in T-and B-lymphocytes exerts a marked reduction in lipopolysaccharide (LPS)-mediated inflammation [43].…”
Section: Beta-glucocerebrosidasementioning
confidence: 76%
See 1 more Smart Citation
“…This inhibition effectively alleviates neuroinflammationinduced dopaminergic neuronal loss in various experimental models, including mouse glioma cells, primary rat microglia, and human microglia cell lines [42]. Furthermore, studies have demonstrated that LRRK2 kinase inhibition attenuates neuroinflammation, gliosis, and cytotoxicity in murine models receiving intracerebral injections of α-syn preformed fibrils, thereby reinforcing the anti-inflammatory potential of LRRK2 kinase inhibition in preclinical settings [43]. Recent investigations employing a chimeric mouse model revealed that replacing mutant LRRK2 with the wild-type variant of the protein in T-and B-lymphocytes exerts a marked reduction in lipopolysaccharide (LPS)-mediated inflammation [43].…”
Section: Beta-glucocerebrosidasementioning
confidence: 76%
“…Furthermore, studies have demonstrated that LRRK2 kinase inhibition attenuates neuroinflammation, gliosis, and cytotoxicity in murine models receiving intracerebral injections of α-syn preformed fibrils, thereby reinforcing the anti-inflammatory potential of LRRK2 kinase inhibition in preclinical settings [43]. Recent investigations employing a chimeric mouse model revealed that replacing mutant LRRK2 with the wild-type variant of the protein in T-and B-lymphocytes exerts a marked reduction in lipopolysaccharide (LPS)-mediated inflammation [43]. Additionally, this genetic alteration rescues dopaminergic neuron loss within the substantia nigra pars compacta, underscoring the profound influence of LRRK2 mutations on the adaptive immune system and its significant role in shaping neuropathological outcomes [44].…”
Section: Beta-glucocerebrosidasementioning
confidence: 85%
“…LRRK2, a major modulator of neuroinflammation involved in the pathogenesis of Parkinson's disease, is upregulated in both depressive (logFC = 0.56) and VDD (logFC = 2.57) patients [47,48]. LRRK2 mutations have been found in individuals without manifest Parkinson's disease, in which compensatory changes in the serotonergic system were described [49].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is extensive evidence that LRRK2 kinase activity modulates PD-relevant neuroinflammatory responses [223][224][225]. Thus, the inhibition of LRRK2 kinase activity is an exciting experimental approach [225,226]. Given such promise, ongoing clinical trials are being conducted [227].…”
Section: Potential Future Therapiesmentioning
confidence: 99%